Kepemimpinan Lintas Budaya di Era Dekolonisasi Manajemen: Menuju Standar Global yang Non-Barat (Fokus: Menciptakan Standar Kepemimpinan yang tidak hanya Berkiblat pada Teori Manajemen Amerika/Eropa) - Miftahul Rizqi; Zam Akhsanu Zahro; Fatihul Muhaimin; Mochammad Isa Anshori (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2026)
The dominance of Western management paradigms in global leadership studies has created homogeneous standards that are less sensitive to non-Western cultural values, while the decolonization of management calls for more contextual, inclusive, and locally-informed approaches. This study aims to analyze the concept of cross-cultural leadership within the framework of management decolonization, identify critiques of Western leadership models, and formulate a conceptual framework for global leadership based on non-Western values. The approach employed is qualitative, drawing on literature review and thematic synthesis of academic publications, international reports, and policy documents relevant to leadership practices in Asia, Africa, and Latin America. The findings reveal that cross-cultural leadership emphasizes collectivism, social harmony, relationality, spirituality, and the integration of local values into decision-making, which significantly diverges from the individualistic and transformational models dominant in the West. These findings underscore the need to reconstruct global leadership standards to be more pluralistic, culturally sensitive, and adaptive to the diversity of multinational organizations. Conceptually, this article contributes an alternative framework for global leadership studies, providing a foundation for managerial practices that respect local cultural values, and offering implications for curriculum development in management education and organizational policies that support inclusivity and sustainability in cross-cultural environments. The abstract reflects the study’s contribution to expanding the literature on cross-cultural leadership through decolonial and indigenous leadership perspectives. Keywords: Cross-cultural leadership, Manajemen decolonization, Non-Western global standards, Indigenous leadership, Postcolonial management, Local cultural values